2018
DOI: 10.1371/journal.pone.0190503
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of the onset of Osgood–Schlatter disease using kinetic analysis of various motions in sports

Abstract: BackgroundSome studies have listed motions that may cause Osgood-Schlatter disease, but none have quantitatively assessed the load on the tibial tubercle by such motions.PurposesTo quantitatively identify the load on the tibial tubercle through a biomechanical approach using various motions that may cause Osgood-Schlatter disease, and to compare the load between different motions.MethodsEight healthy male subjects were included. They conducted 4 types of kicks with a soccer ball, 2 types of runs, 2 types of sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
3
10
0
3
Order By: Relevance
“…These factors can be considered to generate not only OSD, but also its bilateral form in the analyzed case. This thesis corresponds to the findings of Itoh et al, [ 19 ] who argued that movements that significantly stress the lower limb, such as kicking (in football) and 1-legged landing are associated with a higher risk of developing OSD, although these studies were conducted in male athletes.…”
Section: Discussionsupporting
confidence: 87%
“…These factors can be considered to generate not only OSD, but also its bilateral form in the analyzed case. This thesis corresponds to the findings of Itoh et al, [ 19 ] who argued that movements that significantly stress the lower limb, such as kicking (in football) and 1-legged landing are associated with a higher risk of developing OSD, although these studies were conducted in male athletes.…”
Section: Discussionsupporting
confidence: 87%
“… 2 Moreover, the fast knee extension of the support leg at ball impact may have increased the traction stress of the tibial tubercle through the quadriceps femoris muscle and resulted in OSD of the support leg. Additionally, Itoh et al 11 revealed that single-leg landing produced the highest knee extension moment compared with other motions during soccer training. Moreover, the knee extension moment of the support leg during the kicking motion is predicted to be higher than that during running or cutting.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Additionally, higher knee extension moments are seen during a single-leg landing compared with other motions (eg, running or cutting motion) in soccer. 11 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The traction force applied by the patellar tendon to the tibial tubercle apophysis has never been measured experimentally. Itoh et al were the first to estimate the The influence of malalignment on overuse injuries force on the tibial tubercle through gait analysis and musculoskeletal modelling (39). The authors analyzed the knee extension moment in eight patients, during the two most common activities (soccer and basketball) considered as involved in the development of OSD.…”
Section: Osgood-schlatter Diseasementioning
confidence: 99%